2016
DOI: 10.1093/gji/ggw028
|View full text |Cite
|
Sign up to set email alerts
|

Along-strike variations of the partitioning of convergence across the Haiyuan fault system detected by InSAR

Abstract: Oblique convergence across Tibet leads to slip partitioning with the coexistence of strike-slip, normal and thrust motion on major fault systems. A key point is to understand and model how faults interact and accumulate strain at depth. Here, we extract ground deformation across the Haiyuan Fault restraining bend, at the northeastern boundary of the Tibetan plateau, from Envisat radar data spanning the 2001-2011 period. We show that the complexity of the surface displacement field can be explained by the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 52 publications
7
73
0
Order By: Relevance
“…It is the site of two M w ~8 earthquakes in the last century—the 1920 Haiyuan and the 1927 Gulang earthquakes. Except for the estimate of ~10 mm/yr from Daout et al (), previous geodetic studies showed strike‐slip rates of ~4–6 mm/yr along the main Haiyuan Fault (e.g., Cavalié et al, ; Duvall & Clark, ; Jolivet et al, ; Zheng et al, ). Here two profiles HY1 and HY2 across the main Haiyuan Fault give a sinistral rate of ~4–5 mm/yr (Figures e and f) and a shortening rate of ~2–3 mm/yr (Figures S4e and S4f), inconsistent with a present‐day strike‐slip rate of 10 mm/yr.…”
Section: Discussionmentioning
confidence: 89%
“…It is the site of two M w ~8 earthquakes in the last century—the 1920 Haiyuan and the 1927 Gulang earthquakes. Except for the estimate of ~10 mm/yr from Daout et al (), previous geodetic studies showed strike‐slip rates of ~4–6 mm/yr along the main Haiyuan Fault (e.g., Cavalié et al, ; Duvall & Clark, ; Jolivet et al, ; Zheng et al, ). Here two profiles HY1 and HY2 across the main Haiyuan Fault give a sinistral rate of ~4–5 mm/yr (Figures e and f) and a shortening rate of ~2–3 mm/yr (Figures S4e and S4f), inconsistent with a present‐day strike‐slip rate of 10 mm/yr.…”
Section: Discussionmentioning
confidence: 89%
“…A similar, but not identical, pattern of strain partitioning has been interpreted for the Haiyuan Fault and adjacent thrusts, to the east of our study area (102–104°E), by Daout et al . [], based on a combined study of InSAR and GPS data. The two areas are different in terms of the proportions of thrust and strike‐slip deformation and the greater depth of locking further west.…”
Section: Discussionmentioning
confidence: 96%
“…The best fit oblique detachment slips below a locking depth of 26 ± 8 km and has a dip of 17 ± 4° to the SSW. This locking depth is in close agreement with estimates of the seismogenic thickness from robust earthquake depths (~20 km [ Sloan et al ., ]) and with previous interseismic studies of the Haiyuan fault west of 104°E [ Jolivet et al ., ], which is fully locked, in contrast to the creeping section further east [e.g., Jolivet et al ., ; Daout et al ., ]. The best fit horizontal location of the locked‐creeping transition on the fault is constrained to within 9 km and is in agreement with the mapped surface trace of the Haiyuan Fault, implying a vertical or subvertical structure in the seismogenic upper crust.…”
Section: Observationsmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, in the field of active tectonics, these methods allow detection of transient slip along active faults or to image slow, longwavelength, strain rates due to interseismic loading across active faults [e.g. Elliott et al, 2008;Jolivet et al, 2012Jolivet et al, , 2013Bekaert et al, 2015;Rousset et al, 2016;Daout et al, 2016]. c ⃝2018 American Geophysical Union.…”
Section: Introductionmentioning
confidence: 99%